Foot Care Knowledge and Practice Among Type 2 Diabetes Mellitus Patients In Hospital Universiti Sains Malaysia - Chuan, Khaw Yam (2021)
Introduction: Diabetic foot ulcer (DFU) is a chronic disease which causes significant mortality and morbidity to diabetic patients worldwide, especially complication like lower limb amputation. This study aims to determine the level of foot care knowledge and practice among type 2 diabetes mellitus (T2DM) patients and to determine relationship of foot care knowledge or practice with DFU.